Detection of Sarcocystis hominis, Sarcocystis bovifelis, Sarcocystis cruzi, Sarcocystis hirsuta and Sarcocystis sigmoideus sp. nov. in carcasses affected by bovine eosinophilic myositis - Selene Rubiola; Gastón Moré; Tiziana Civera; Andrew Hemphill; Caroline F. Frey; Walter Basso; Irene Colasanto; Davide Vercellino; Marta Fidelio; Mauro Lovisone; Francesco Chiesa (Food and Waterborne Parasitology, 2024)
Bovine eosinophilic myositis is an inflammatory myopathy characterized by multiple focal or diffuse grey to green patches leading to condemnation of affected carcasses. Although its etiology is still uncertain, there is evidence that Sarcocystis species may play a role in the development of eosinophilic myositis. The goal of the present study was to identify Sarcocystis spp. in intralesional and extralesional tissues of condemned cattle carcasses, in order to evaluate the possible role of different bovine Sarcocystis spp. in the etiology of bovine eosinophilic myositis. Muscle samples (n = 100) of 26 affected carcasses were collected in Northern Italy. One to five samples with lesions and two aliquots of tissue without lesions were collected from each carcass; lesions were grossly categorized in green focal lesions and green diffuse patches. Genomic DNA was extracted and analyzed by multiplex-PCR targeting different Sarcocystis spp. Unidentified species were characterized morphologically (light microscopy, histology), ultrastructurally (scanning and transmission electron microscopy) and on the molecular level (complete 18S rRNA gene and partial cox1 gene sequencing). A bovine eosinophilic myositis prevalence of 0.017% was visually assessed by routine carcass inspection between 2014 and 2019 in Italy (184/1,108,150 slaughtered cattle). Out of 26 carcasses, 25 revealed the presence of at least one Sarcocystis species (96.2%). The presence of Sarcocystis spp. DNA was significantly more frequent in intralesional than in extralesional samples. Considering the different species, Sarcocystis bovifelis and Sarcocystis hominis were significantly more frequent in intralesional (41.7% and 50%, respectively) than in extralesional samples (1.9% and 15.4%, respectively), while there was no significant difference between the presence of Sarcocystis cruzi and Sarcocystis hirsuta in intralesional (27.1% and 2.1%, respectively) and extralesional (30.8% and 1.9%, respectively) samples. The presence of an unnamed Sarcocystis sp. showing thick-walled (3.7–5.4 μm) cysts with densely packed, flattened, undulating and narrow protrusions, which showed an S-shape in side view, was recorded in the diaphragm of two carcasses. Genomic DNA from individual sarcocysts isolated from the diaphragm was successfully amplified and further sequenced. Sequence comparison revealed <94.6% and 83.4% identity at 18S rRNA and cox1 genes, respectively, with other named Sarcocystis spp., while the phylogenetic analysis clearly separated the unnamed Sarcocystis sp. from the other Sarcocystis spp. using cattle as intermediate hosts. The present study contributes to the understanding of the importance of different Sarcocystis spp. in the pathogenesis of bovine eosinophilic myositis. The results emphasize the association of Sarcocystis hominis and Sarcocystis bovifelis with bovine eosinophilic myositis and highlight the presence of a new Sarcocystis sp. using cattle as intermediate hosts. The name Sarcocystis sigmoideus sp. nov. is proposed for the newly described Sarcocystis species.